The dimension of the pore space in sponges - Silva, L. H. F. [UNESP]; Yamashita, Marcelo Takeshi [UNESP] (Iop Publishing Ltd, 2009)
A simple experiment to reveal the dimension of the pore space in sponges is proposed. This experiment is suitable for the first year of a physics or engineering course. The calculated dimension of the void space in a sponge of density 16 mg cm(-3) was 2.948 +/- 0.008.